PENGARUH CITRA MEREK, KEMUDAHAN TRANSAKSI DAN LOKASI TERHADAP KEPUTUSAN MENJADI ANGGOTA KOPERASI SYARIAH BMT BISMA TANGERANG - Nur Jamaludin; Rohadatul A’is (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to determine the effect of brand image, ease of transaction and location on the decision to become a member of the Sharia Cooperative BMT BISMA Kelapa Dua Tangerang. This study took the population of members of the BMT BISMA Kelapa Dua Sharia Cooperative with purposive sampling technique. The method used is descriptive quantitative by conducting statistical tests consisting of validity, reliability, classical assumption tests, multiple regression tests and hypothesis testing by testing brand image variables, transaction convenience and location partial or simultaneous influence on the decision. The findings of this study indicate that the ease of transaction and location variables have a positive and significant influence on the decision to become a member of the BMT BISMA Sharia Cooperative. While the brand image variable does not have a significant influence on the decision to become a member of the BMT BISMA Sharia Cooperative.